A phenomenological study exploring the first year experiences of neophyte nurses in Taiwan - Lee, Li-Hung. (2009)
The high neophyte nurses’ turnover rate has been recognized as one of the most important issues in Taiwan’s nursing profession. Although Taiwanese nursing researchers have started to investigate the reasons why neophyte nurses’ leave their jobs, most of the studies use quantitative research methodologies. Consequently, we still know very little about how neophyte nurses experience their first year after graduating. Therefore, in order to comprehensively understand more about the phenomenon of neophyte nurses’ experiences following graduation, the research question was posed to guide the study: How do neophyte nurses experience their first year after graduating in Taiwan? The aim of the study was to explore the first year experiences of Taiwanese neophyte nurses.